(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Innovative concrete known as Self Consolidating Concrete (SCC) does not require vibration for placement or compaction. Even in the midst of crowded reinforcement, it can flow under its own weight, completely filling forms and attaining full compaction. Self- Consolidating Concrete has unique characteristics from regular concrete. The workability characteristics of self-consolidating concrete containing fly ash and silica fume with super plasticizer as the silica fume are examined in this research. Workability tests including the slump flow, V-funnel, and L-Box tests are used to assess the workability properties of SCC such as filling ability, passing ability, and segregation resistance. The cubes’ compressive strength at 7 and 28 days was also measured, and it was discovered that the mixture had an excellent compressive strength.